REVIEW: COMPARATIVE SYSTEM ANALYSIS OF OYSTER (Crassostrea sp) BREEDING IN JAPAN AND INDONESIA - Ramadhan, Luthfi Naufal; Junianto , Junianto (Jurnal Perikanan Unram, 2025)
Oysters (Crassostrea sp.) are high-value aquaculture commodities with significant economic and ecological potential. Japan and Indonesia are both maritime countries with vast marine resources, yet they differ considerably in their oyster farming systems. This study aims to conduct a comparative analysis of oyster cultivation systems in the two countries, focusing on farming methods, technology, environmental management, policy support, and productivity. A qualitative descriptive approach was employed through a literature review of various scientific sources and secondary data published over the past ten years. The results show that Japan has developed a modern and sustainable farming system, utilizing automation, real-time water quality monitoring, and strong, integrated policy support. In contrast, Indonesia still relies on traditional farming methods, with limited access to technology and weak environmental management, while policy implementation remains suboptimal. This comparison is essential as a foundation for evaluating and formulating strategic development plans for oyster aquaculture in Indonesia. A collaborative effort between the government, academics, and industry stakeholders is needed to strengthen the transition toward an efficient, adaptive, and sustainable oyster farming system in the future.